2007
DOI: 10.1186/1471-2091-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyamines and synthetic polyamine-analogues on the expression of antizyme (AtoC) and its regulatory genes

Abstract: BackgroundIn bacteria, the biosynthesis of polyamines is modulated at the level of transcription as well as post-translationally. Antizyme (Az) has long been identified as a non-competitive protein inhibitor of polyamine biosynthesis in E. coli. Az was also revealed to be the product of the atoC gene. AtoC is the response regulator of the AtoS-AtoC two-component system and it functions as the positive transcriptional regulator of the atoDAEB operon genes, encoding enzymes involved in short chain fatty acid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
0
24
0
2
Order By: Relevance
“…That drastic difference in histamine, spermidine and spermine concentrations may represent a system of regulation in the presence of one or several BAs. Very few data to date have suggested that BAs possess self-regulatory activities; however, it was demonstrated that the protein AtoC/Az (an ornithine decarboxylase inhibitor) from E. coli was regulated at a transcriptional level in the presence of BAs [36]. …”
Section: Discussionmentioning
confidence: 99%
“…That drastic difference in histamine, spermidine and spermine concentrations may represent a system of regulation in the presence of one or several BAs. Very few data to date have suggested that BAs possess self-regulatory activities; however, it was demonstrated that the protein AtoC/Az (an ornithine decarboxylase inhibitor) from E. coli was regulated at a transcriptional level in the presence of BAs [36]. …”
Section: Discussionmentioning
confidence: 99%
“…The ability of the previously synthesized constructs 11,21 carrying lacZ fused to either of the promoters of the atoSC system (i.e., the atoC and the atoDAEB promoter) to respond to the compounds of the present study was evaluated in E. coli strain BW25113 (Fig. 2).…”
Section: Chemistrymentioning
confidence: 99%
“…9 We have recently reported the regulation of the AtoSC system by polyamines and histamine, as cellular components that enable pathogenic bacteria to survive and overcome host defence mechanisms. [10][11][12] Putrescine, the non-natural diamine 1,3-diaminopropane and their synthetic analogues elicited a pronounced atoC transcriptional activation, without activating neither the atoDAEB operon promoter nor atoS. 11 Histamine, a biogenic amine, elicited a polyamine-mediated inductive phenotype and induced atoC expression, without activating the atoDAEB operon promoter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the poly electrolyte nature of xanthan and Arabic gums (Makri & Doxastakis, 2006;Garcıá-Ochoa, Santos, Casas, & Gómez, 2000), the flexible film networks formed by the PSPI-XG/GA interactions around the bubbles in the solution could have been negatively affected by the addition of sodium chloride and may have contributed further to the repulsive forces resulting in reduced foaming properties. At lower pH conditions increase in NaCl concentration causes an increase in protein stability (Lindman et al, 2006), which results in unfolding, viscosity, solubility and aggregation of proteins, which in turn affect foaming properties by increasing the solvent surface tension,decreasing the solubility of nonpolar molecules and ultimately strengthening hydrophobic interactions (Cheftel et al, 1985;Mao, Sheng, & Pan, 2007). Therefore salt treatment conditions under much lower pH conditions could most likey improve the foaming properties.…”
Section: Effect Of Salt Concentration On Foaming Capacity and Stabilitymentioning
confidence: 99%